Fabric, method for manufacturing the same, and bed pad and mattress using the same

By adhering finely-formed cellulose fibers to fabric constituent yarns, the fabric achieves improved recovery and deformation resistance, addressing the challenges of soft texture and environmental sustainability in existing textile products.

JP2025047835APending Publication Date: 2025-04-03AOSHIMA GRACE JAPAN CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023156577
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing fabrics used in textile products, such as mattress pads and mattresses, face challenges in achieving both soft texture and environmental sustainability, with concerns about increased environmental impact and difficulty in recycling.

Method used

A fabric is developed by adhering finely-formed cellulose fibers with a fine content of 90% or more to fabric constituent yarns using a binder resin for fiber adhesion, which improves recovery and reduces environmental impact.

Benefits of technology

The resulting fabric exhibits improved recovery rates and deformation resistance under load, making it suitable for use in mattress pads and mattresses, while also being biodegradable and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047835000001_ABST
    Figure 2025047835000001_ABST
Patent Text Reader

Abstract

To provide a fabric capable of improving extension recovery properties while using a fabric constituent yarn in which a versatile fiber is used.SOLUTION: In a fabric having a woven texture or knitted texture, a fine cellulose fiber containing 90% or more of a fine component is bonded to a fabric constituent yarn by a binder resin for fiber bonding. A manufacturing method of the fabric includes the steps of: constituting a fabric to be processed having the woven texture or knitted texture in advance; adding 0.5 to 1 wt.% of the binder resin for fiber bonding to a fine cellulose fiber dispersion liquid which contains 1 wt.% of fine cellulose fiber containing 90% or more of the fine component and contains water as a dispersant, and stirring the resultant mixture; immersing the fabric to be processed in the fine cellulose fiber dispersion liquid contained in the binder resin for fiber bonding for 3 to 5 seconds to impregnate the fibers of the fabric to be processed with the fine cellulose fibers; and removing the dispersant constituting the dispersion liquid by drying.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fabric and a method for producing the same, and to a mattress pad and a mattress pad using the fabric, and in particular to the fabric having finely divided cellulose fibers attached thereto. [Background technology]

[0002] Until now, fabrics used in textile products have been improved in various ways to improve their stretchability and elongation recovery in order to achieve a soft feel (see Patent Document 1). These fabrics are particularly suitable for improving the feel (comfort when worn or worn) by improving their stretchability, but they use fibers with multiple different properties and contain a large amount of resin compounds, which makes recycling difficult and increases the environmental load, raising concerns.

[0003] Also, a multi-layered fabric using crimped fibers has been developed to provide a soft texture (Patent Document 2). However, because it has a multi-layered structure, it is assumed that it will be bulky, making it difficult to use in conventional products such as mattress pads and futons. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-133147 A [Patent Document 2] WO2018 / 216572 publication Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above, the present invention aims to provide a fabric that can improve recovery while using fabric constituent yarns made of commonly used fibers, and to provide a mattress pad and a mattress pad utilizing the same. [Means for solving the problem]

[0006] Therefore, as a result of intensive research, the present inventors have completed a fabric that can improve recovery properties to an appropriate level by using fine cellulose fibers.

[0007] In other words, the present invention relating to a fabric is a fabric having a woven or knitted structure, characterized in that microfibrillated cellulose fibers having a fine content of 90% or more are bonded to the fabric-constituting yarns by a fiber bonding binder resin.

[0008] As the fibers used for the fabric-constituting yarns, natural fibers such as cotton, wool, or silk can be used, and in addition, commonly used resin fibers such as polyester fibers, acrylic fibers, and nylon fibers can be used. Since the finely divided cellulose fibers are finely divided cellulose fibers made from pulped non-wood fibers, wood fibers, etc., the combination of the finely divided cellulose fibers with the fabric-constituting yarns made from the natural fibers can reduce the environmental load. In addition, since the finely divided cellulose fibers themselves have sufficient strength, by bonding the finely divided cellulose fibers to the fabric-constituting yarns via a fiber bonding binder resin, recovery can be obtained even in a state where a fabric having a woven or knitted structure is constituted by fabric-constituting yarns made from general fibers.

[0009] On the other hand, the present invention relating to a method for producing a fabric is characterized by comprising the steps of: preliminarily constructing a target fabric having a woven or knitted structure; adding 0.5 to 1% by weight of a fiber bonding binder resin to a microfibrillated cellulose fiber dispersion containing 1% by weight of microfibrillated cellulose fibers having a fine content of 90% or more in water as a dispersion medium and stirring the mixture; immersing the target fabric in the microfibrillated cellulose fiber dispersion containing the fiber bonding binder resin for 3 to 5 seconds to impregnate the fibers of the target fabric with the microfibrillated cellulose fibers; and removing the dispersion medium constituting the dispersion by drying.

[0010] Examples of textile products using the above-mentioned fabric include mattress pads and mattress futons. A mattress pad is characterized in that a plurality of sheets of the fabric are laminated and sewn together at appropriate positions to form an integrated unit, while a mattress futon is characterized in that at least one sheet of the fabric is disposed on both the front and back sides, with cotton filled between them and sewn together at appropriate positions.

[0011] Since the fabric according to the present invention can obtain an improved recovery rate, it is suitable for use as a mattress such as a mattress pad or a mattress. Effect of the Invention

[0012] According to the present invention, for a fabric using fabric-constituting yarns using generally used fibers, it is possible to maintain a state in which pulverized cellulose fibers having a fine content of 90% or more are attached to the fabric-constituting yarns, and as a result, it is possible to provide a fabric with improved recovery. Furthermore, by using such a fabric, it is possible to provide a mattress pad and a mattress mattress with good recovery. [Brief description of the drawings]

[0013] [Figure 1] 1 is a micrograph showing the results of a washing test of an embodiment of the present invention and a comparative example, showing the state before the washing test. [Diagram 2]1 is a micrograph showing the results of a washing test of an embodiment of the present invention and a comparative example, showing the state after one washing test. [Diagram 3] 1 is a micrograph showing the results of a washing test of an embodiment of the present invention and a comparative example, showing the state after three washing tests. [Figure 4] 1 is a micrograph showing the results of a washing test of an embodiment of the present invention and a comparative example, showing the state after 10 washing tests (however, the comparative example shows the state after 3 washing tests). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, an embodiment of the present invention will be described. Note that the embodiment is an example of the present invention. The scope of the present invention is not limited to the scope of the embodiment.

[0015] The fabric of the present invention is one in which pulverized cellulose fibers having a fine content of 90% or more are bonded to fabric-constituting yarns with a fiber-bonding binder resin.

[0016] The microfibrillated cellulose fibers of the present invention can be made from one or more materials selected from, for example, wood pulp made from broadleaf trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broke, etc. Pulps other than waste paper pulp are preferred because they have a higher purity of cellulose fibers and less impurities other than cellulose fibers than waste paper pulp.

[0017] Prior to defibration of the fine cellulose fibers of the present invention, the fine cellulose fibers can be treated by a chemical method as a pretreatment for defibration. Examples of pretreatment by a chemical method include hydrolysis of polysaccharides with an acid (acid treatment), hydrolysis of polysaccharides with an enzyme (enzyme treatment), swelling of polysaccharides with an alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), reduction of polysaccharides with a reducing agent (reduction treatment), oxidation with a TEMPO catalyst (oxidation treatment), and esterification with phosphorus oxoacid (chemical treatment). If enzyme treatment, acid treatment, or oxidation treatment is performed prior to defibration, defibration becomes easier and the fine cellulose fibers have excellent homogeneity.

[0018] The defibration of cellulose fibers can be carried out by using one or more means selected from homogenizers such as high-pressure homogenizers and high-pressure homogenizing devices, high-speed rotary homogenizers, grinders, mill-type friction machines such as grinders and grinders, refiners such as conical refiners and disc refiners, single-shaft kneaders, multi-shaft kneaders, various bacteria, etc.

[0019] The fine fraction of the fibrous cellulose fibers of the present invention indicates the ratio of fibers with a fiber length of 0.2 mm or less when the length-weighted average fiber length of the fibrous cellulose fibers of the present invention is measured using an L&W Fiber Tester Plus fiber shape analyzer (manufactured by Lorentzen) in accordance with JIS P 8226-2 Part 2.

[0020] The fine content of the fibrous cellulose fiber of the present invention is preferably 90% or more, more preferably 92% or more. If it is less than 90%, relatively long fibers remain, which tends to cause fiber twisting when mixed and stirred with a fiber bonding binder in a subsequent process, impairing uniform application of the coating liquid to the fabric.

[0021] The fine cellulose fibers attached to the yarns constituting the fabric are in a state of straddling the surrounding yarns constituting the fabric, and therefore the gaps between the yarns constituting the fabric can be reduced, thereby improving the heat retention of the fabric. Although the fine cellulose fibers are gradually detached from the yarns constituting the fabric by washing, etc., since the fine cellulose fibers are derived from plants, they are highly biodegradable and do not cause soil or water pollution, thereby reducing the environmental load.

[0022] Since the fine cellulose fibers themselves have water retention properties, the fabric as a whole exhibits good water retention properties in addition to those of the fabric-constituting yarns. In addition, since the fine cellulose fibers have sufficient strength, the recovery properties can be improved by attaching them to the fabric-constituting yarns, but by adhering them to the fabric-constituting yarns via a fiber bonding binder resin, recovery properties can be obtained even in the case where the fabric has a woven or knitted structure and is made of fabric-constituting yarns using general fibers.

[0023] The yarns constituting the fabric may be made of not only the natural fibers listed above, but also general resin fibers such as polyester fibers, acrylic fibers, and nylon fibers. For the purpose of improving recovery, a fabric made of yarns constituting the fabric made of fibers other than those listed as examples may be used.

[0024] As the fiber bonding binder resin used to attach the fine cellulose fibers to the fabric (fabric constituent yarn), general-purpose emulsion binder resins such as acrylic acid esters and ethylene-vinyl chlorides can be used, as well as emulsion binder resins such as vinyl chloride, vinylidene chloride, polyester, ethylene-vinyl acetate, and ethylene-vinyl acetate-vinyl chloride. These fiber bonding binder resins can attach the fine cellulose fibers to the fabric constituent yarns while maintaining their flexibility even after dehydration by drying. In addition, instead of the above-mentioned emulsion binder resins, an isocyanate-based crosslinking agent (Dystone Fixer XA manufactured by Matsui Shikishoku Kagaku Kogyosho) used as a printing assistant can be used. Furthermore, a mixture of the above-mentioned binder and crosslinking agent may be used. The crosslinking agent to be mixed with the binder is appropriately selected from melamine, isocyanate compounds, epoxy compounds, etc. according to the type of binder. EXAMPLES

[0025] <Example 1> Example 1 of the fabric having microfibrillated cellulose fibers attached thereto was prepared by the following procedure. (Preparation of Micronized Cellulose) The linter pulp sheet was soaked in water and mixed at a concentration of 2.7% by mass. The mixture was treated and ground in a stone mill grinder (product name: Masscolloider) manufactured by Tokuyama Electric Co., Ltd., to obtain a micronized cellulose dispersion with a fine content of 93%. (Preparation of fine cellulose blended coating solution and coated fabric) The above-mentioned fine cellulose fiber dispersion was mixed with a binder resin for fiber adhesion to prepare a dispersion, and a fabric (target fabric) previously prepared as a structure having a woven fabric structure was immersed in the dispersion and then dried. Cotton was used as a natural fiber for the fibers constituting the fabric yarns. The dispersion had a blending ratio of 1% by weight of fine cellulose fiber per 1 L of water, and the binder resin for fiber adhesion added was Dystone Fixer XA manufactured by Matsui Shikishoku Kogyosho Co., Ltd., which was added at 1% by weight per 1 L of dispersion medium (water). The target fabric was immersed for 3 to 5 seconds, taken out, mechanically squeezed, and then dried for 10 minutes in a drying oven maintained at 90°C.

[0026] <Example 2> In Example 2, the fiber adhesive binder resin (Dystone Fixer XA manufactured by Matsui Shikishoku Kagaku Kogyosho) was added in an amount of 5% by weight by the same procedure as in Example 1. The other conditions were not changed.

[0027] <Comparative Example> For comparison, the comparative examples were made using the same cotton yarn as the fabric constituent yarn and were finished with the same weaving machine to have the same weave.

[0028] <Performance test> The performance test was performed by measuring mechanical compression performance and recovery performance. The test piece used in the test was a futon mattress made of the fabric of Example 1 (containing 1% by weight of binder), and the fabric (cotton gauze) was made into a bag shape, cotton (real cotton) was enclosed in it, and the entire surface was quilted. The test piece was a quadrilateral of 22 cm x 22 cm and had a thickness of 1.5 cm (however, only the quilted part was 1.0 cm). The specific content of the test was that the test piece was folded in four and a 0.5 kg backing plate (10 cm x 10 cm) was placed on it to set it in the initial state, and the thickness (h0) at this time was measured, and then a load of 28 kg was added and compressed for 5 minutes to measure the thickness (h1), and the thickness (h2) was measured when the load was released immediately after and left for 5 minutes, to calculate the compression rate (%) and recovery rate (%).

[0029] The calculation method was as follows. Compression ratio (%) = (h0-h1) / h0 x 100 Recovery rate (%)=(h2-h1) / (h0-h1)×100 The individual compression rates and recovery rates calculated from the measurement results are as shown in the table below.

[0030] [Table 1]

[0031] Referring to the above results, the test piece according to Example 1 has a smaller compression ratio than the comparative example, but a larger recovery ratio. The recovery ratio is well above 70%. The other comparative example has a recovery ratio less than 70%. This result shows that the test piece made of the fabric of the example is less likely to deform under an external load and is easy to restore. This means that in textile products that are subjected to load, such as mattress pads and mattresses, the resistance to deformation when subjected to load is improved and the recovery performance is improved. In particular, when used as a mattress, it prevents the body from sinking and can maintain elasticity for a long period of time.

[0032] <Washing test> A washing test was carried out in the above-mentioned Example 1, Example 2 and Comparative Example. In the test, a fabric (gauze fabric) made of plain weave cotton constituent yarn was prepared as a target fabric, and agitation was carried out for 30 minutes in agitator with detergent dosage to simulate washing conditions, and agitation was carried out for 30 minutes in water to simulate rinsing. The above-mentioned one set was counted as one wash, and micrographs were taken at angular magnifications of 500x and 2000x after 0 wash (before washing), 1 wash, 3 washes, and 10 washes, respectively. In Comparative Example 1, since no finely divided cellulose fibers were attached (no binder was used), there was basically no change in condition even after washing, but the test was carried out in order to confirm the change in the surface condition of the fabric constituent yarn after washing, and to compare the adhesion state of the finely divided cellulose fibers on the surface of the fabric constituent yarn in Example 1 or 2.

[0033] These micrographs are shown in Figs. 1 to 4. In the figures, "untreated" refers to a comparative example, "1% binder" refers to Example 1, and "5% binder" refers to Example 2. "x500" and "x2000" indicate the magnification of the microscope. As is clear from these micrographs, the fine cellulose fibers remain attached to the fabric-constituting yarns via the fiber-bonding binder resin regardless of the number of washes. In particular, no significant change in the attachment state was observed even after 10 wash experiments. In addition, the amount of the fiber-bonding binder resin added was 1% by weight in Example 1 and 5% by weight in Example 2, but no particular difference was found between the two. Therefore, it is determined that the attachment state of the fine cellulose fibers can be maintained if the fiber-bonding binder resin is 1% by weight or more.

[0034] Moreover, whether the fiber bonding binder resin is 1% by weight or 5% by weight, the adhesion rate of the fine cellulose fibers, as determined from the micrographs, is 1% or more of the total surface area of ​​the fabric-constituting yarns. It can also be seen that the fine cellulose fibers are less likely to remain on smooth surfaces, and tend to remain in areas where the fabric-constituting yarns intersect in a complex manner. Therefore, it is considered that the adhesion rate of the fine cellulose fibers is improved in fabrics in which the fabric-constituting yarns intersect in a complex manner.

[0035] <Summary> As described above, a fabric in which fine cellulose fibers with a fine content of 90% or more are bonded to fabric-constituting yarns with a fiber-bonding binder resin has good resistance to deformation under load and improved recovery performance. When used in a mattress pad or a futon, this reduces the sinking of the user's body and improves the recovery function, making it possible to maintain the effect for a long period of time. Note that the fabric used in the experiment had a woven structure, but it is clear from the results of the above experiment that the same effect can be obtained with a knitted fabric.

Claims

1. A fabric having a woven or knitted structure, characterized in that pulverized cellulose fibers having a fine content of 90% or more are bonded to fabric-constituting yarns by a binder resin for bonding fibers.

2. 2. The fabric according to claim 1, wherein the fine cellulose fibers are attached to an area of ​​1% or more of the total surface area of ​​the yarn constituting the fabric.

3. The fabric according to claim 1, wherein when a plurality of sheets are stacked and folded in four, the recovery rate calculated from the thickness when compressed and the thickness 5 minutes after releasing the compression is 70% or more.

4. Prefabricating a target fabric having a woven or knitted structure; a step of adding 0.5 to 1% by weight of a binder resin for fiber adhesion to a microfibrillated cellulose fiber dispersion containing 1% by weight of microfibrillated cellulose fibers having a fine content of 90% or more in water as a dispersion medium, and stirring the mixture; a step of immersing the target fabric in the dispersion of fine cellulose fibers contained in the binder resin for fiber bonding for 3 to 5 seconds to impregnate the fibers of the target fabric with the fine cellulose fibers; a step of removing the dispersion medium constituting the dispersion liquid by drying; A method for producing a fabric, comprising:

5. A mattress pad using the fabric according to any one of claims 1 to 3, The mattress pad is characterized in that a plurality of sheets of the fabric are laminated and sewn together at appropriate positions to form an integrated unit.

6. A mattress using the fabric according to any one of claims 1 to 3, The mattress is characterized in that at least one sheet of the fabric is arranged on both the front and back sides, and is sewn at appropriate positions with cotton enclosed between them.

Citation Information

Patent Citations

  • Manufacturing method of elastic fabric

    JP2017133147A

  • Multilayer structured fabric and fiber product

    WO2018216572A1